Sounding out horse mussel sediment thickness: an integrated data approach - Sheehy, Jack; Bates, Richard; Bell, Michael; Porter, Jo (Frontiers in Marine Science, 2024)
Horse mussel beds are listed as a Priority Marine Feature (PMF) in Scotland for their influence in creation of diverse benthic communities and ecosystem services. They are also recognised for their importance in marine carbon sequestration. Unfortunately, there is a paucity of data on horse mussel bed carbon stocks and sediment thickness. There are also significant financial and logistical barriers with which to address these data gaps. This study investigates the robustness of Sub-Bottom Profiling (SBP) as a cost-effective method to quantify horse mussel sediment thickness across a landscape. Integrating SBP and Drop-Down Video (DDV) data, this study also details an integrated approach to investigate the links between horse mussel habitat health and sediment thickness. With the addition of abiotic data, this study uses Structural Equation Modelling (SEM) to elucidate key relationships between abiotic factors, biotic variables, and sediment thickness. There is a significant positive correlation of horse mussel habitat health and sediment thickness. Average horse mussel sediment thickness, across all measures of habitat health, was 1.37m. This substantially increases previous estimates of horse mussel sediment thickness, and potential value to climate change mitigation through blue carbon frameworks. Abiotic and biotic factors had separate and significant determining effects for horse mussel bed sediment thickness.